Respuesta :

Lanuel

Answer:

I. x = -1

II. y = 1

Step-by-step explanation:

Given the following algebraic expressions;

9x + 10y = 1 .......equation 1

9x - 6y = -15 ......equation 2

To solve using the elimination method, we would subtract eqn 1 from eqn 2.

(9x - 9x) + (-6y - 10y) = (-15 - 1)

0x - 16y = -16

-16y = -16

16y = 16

y = 16/16

y = 1

Next, we would find the value of x;

From eqn 1;

9x + 10y = 1

Substituting the value of y, we have;

9x + 10(1) = 1

9x + 10 = 1

9x = 1 - 10

9x = -9

x = -9/9

x = -1

ACCESS MORE